Evaluating Transnational NGOs
XIV, 271 p. 2 illus.
Keywords: Critics question the representativeness of NGOs, the democratic quality of their internal procedures, and their accountability to the wider public. This volume, written jointly by academics and practitioners, clarifies the issues at stake and controversially discusses proposals for reform.